Attracting Chrysopidae With Plant Volatiles for Lace Bug (Hemiptera: Tingidae) Control in Rhododendrons and Azaleas. Issue 5 (1st September 2020) - Graham, Katerina Velasco; Choi, Man-Yeon; Lee, Jana C
Abstract: The azalea lace bug ( Stephanitis pyrioides Scott) (Hemiptera: Tingidae) is an invasive pest of rhododendrons and azaleas (Ericaceae: Rhododendron ), which feeds on the underside of leaves causing chlorosis, reduced photosynthesis, and even plant death. While insecticides can control this pest, growers, landscape managers, and homeowners have requested softer alternatives. Augmentative release of predatory green lacewing Chrysoperla sp. (Neuroptera: Chrysopidae) eggs and larvae has reduced S. pyrioides, but large-scale implementation may not be practical nor cost-effective. Attracting naturally occurring Chrysopidae with plant volatiles may be an economical and convenient option. In this study, we tested whether volatile blends 1) attracted Chrysoperla sp., and 2) controlled S. pyrioides populations on Rhododendron spp. in farm or urban landscapes. Experimental plots contained different multicomponent lures placed aboveground next to infested plants. Adult Chrysoperla sp., other natural enemies, and S. pyrioides from egg to adult stages were monitored in both farm and urban landscapes for two summers. Overall, two out of three volatile blends consistently attracted Chrysoperla sp. to sticky traps near baited plants. Methyl salicylate + acetic acid + 2-phenylethanol (methyl salicylate blend) and acetophenone + acetic acid + 2-phenylethanol (acetophenone blend) captured more adult Chrysoperla sp. than control traps in farm landscapes. However, only the acetophenone blend was associated with a slight reduction of S. pyrioides . Additional research is needed to determine whether the phenology of the first generation of both species are synchronized for effective season biological control in the Pacific Northwest.